Empirical estimation of the multiplicative effects of steel industry in Macedonia by using input-output model - Darko Lazarov; Mitko Kocovski (UTMS Journal of Economics, 2016)
The main goal of the paper is quantitative and scientifically based economic assessment of basic metal industry and its importance for the national economy. The empirical assessment involves exploring the direct effects (the contribution of the steel industry to GDP and economic growth, export, employment, taxes and corporate - social responsibility) and more important estimating the multiplicative effects (indirect through the chain of suppliers and induced by the effect of final household's consumption) that the industry generates in the national economy by the reproduction processes. The economic impact methodology based on input-output model is applied to estimate the multiplicative effects. Furthemore, the empirical analysis of economic and financial indicators is done to capture the performance of steel industry in Republic of Macedonia. This type of studies based on scientific and methodological foundation is very usefull tool in creation the national industrial policy.
Keywords: L61; D24; 330; economic impact analysis; input-output model; basic metal industry